Reframing Cultural Heritage Policy Through Place-Based Perspectives: The Evolution of China’s ICH Governance Amid Historical Continuity and Global Convergence - Jing Li; Xiangling Wu; Yanan Du (Land, 2025)
This study explores the evolution of China’s intangible cultural heritage (ICH) governance through the lens of discursive institutionalism, with a specific focus on how institutional discourse and arrangements shape the spatial configuration and symbolic meaning of ICH-related landscapes. By analyzing policy discourse, governance actors, resource mobilization, and regulatory mechanisms, the study traces the transition from community-led practices to increasingly formalized and spatialized systems under the influence of the 2003 UNESCO Convention. Drawing on a combination of historical policy analysis and place-specific institutional insights, the research finds that while institutional reforms have enhanced administrative coherence and international alignment, they have also at times disrupted vernacular meanings and weakened residents’ place-based cultural attachments. Conversely, localized revitalization initiatives can foster community resilience and landscape justice. These findings are derived from an interpretive synthesis of institutional trajectories and spatial governance practices. Overall, the study contributes to the theoretical integration of discursive institutionalism and cultural geography, offering new insights into heritage governance and sustainable cultural planning in rapidly urbanizing contexts.